1980
DOI: 10.1042/bj1900395
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine and amino acid content, and activity of polyamine-synthesizing decarboxylases, in liver of streptozotocin-induced diabetic and insulin-treated diabetic rats

Abstract: 1. Concentrations of polyamines, amino acids, glycogen, nucleic acids and protein, and activities of ornithine decarboxylase and S-adenosylmethionine decarboxylase, were measured in livers from control, streptozotocin-diabetic and insulin-treated diabetic rats. 2. Total DNA per liver and protein per mg of DNA were unaffected by diabetes, whereas RNA per mg of DNA and glycogen per g of liver were decreased. Insulin treatment of diabetic rats induced both hypertrophy and hyperplasia, as indicated by an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…In skeletal muscle and in the liver, the BCAAs were higher at both ages, although the difference was not always statistically significant. The increase in BCAAs in this model of type 2 diabetes is consistent with reports of type 1 diabetes by Bloxam (1972) and Brosnan et al (1980Brosnan et al ( , 1983 in streptozotocin-diabetic rats. Isoleucine, leucine, and valine are essential amino acids.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In skeletal muscle and in the liver, the BCAAs were higher at both ages, although the difference was not always statistically significant. The increase in BCAAs in this model of type 2 diabetes is consistent with reports of type 1 diabetes by Bloxam (1972) and Brosnan et al (1980Brosnan et al ( , 1983 in streptozotocin-diabetic rats. Isoleucine, leucine, and valine are essential amino acids.…”
Section: Discussionsupporting
confidence: 91%
“…In our model of type 2 diabetes, glutamine was lower in plasma, liver, and skeletal muscle; alanine concentrations were comparable to the controls in plasma and liver, but levels in the muscle were higher at both 5 and 11 weeks. In streptozotocindiabetic rats, Williamson et al (1967) and Brosnan et al (1980) found decreased levels of both alanine and glutamine in plasma. Hundal et al (1992) found a reduction in intrasarcolemmal glutamine levels in streptozotocin-diabetic rats.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This result is consistent with previous observations (Brosnan et al, 1980;Zulak et al, 2008). As important insulin secretatogues, BCAAs exert a regulatory influence on proteolysis and thus play important roles in building body organs (Brosnan et al, 1983).…”
Section: Target Metabolites Analysis Of Serum and Urine Samplessupporting
confidence: 94%
“…It has been reported that insulin induced hypertrophy and hyperplasia in livers of diabetic rats 26 and caused a concomitant increase in the activity of some enzymes. 27 Probably for this reason the trend of the INS-STZ group in the score plot of liver tissue extract is not consistent with those of the urine and serum samples described above.…”
Section: H Nmr Spectroscopic and Pattern Recognition Analysis Of Livermentioning
confidence: 85%